Design of a ferrite rod antenna for harvesting energy from medium wave broadcast signals. Issue 12 (23rd December 2013) - Dyo, Vladimir; Ajmal, Tahmina; Allen, Ben; Jazani, David; Ivanov, Ivan
Abstract : Radio frequency (RF) energy harvesting is an emerging technology that has the potential to eliminate the need for batteries and reduce maintenance costs of sensing applications. The antenna is one of the critical components that determines its performance and while antenna design has been well researched for the purpose of communication, the design for RF energy harvesting applications has not been widely addressed. The authors present an optimised design for such an antenna for harvesting energy from medium wave broadcast transmissions. They derive and use a model for computing the optimal antenna configuration given application requirements on output voltage and power, material costs and physical dimensions. Design requirements for powering autonomous smart meters have been considered. The proposed approach was used to obtain the antenna configuration that is able to deliver 1 mW of power to 1 kΩ load at a distance of up to 9 km, sufficient to replace batteries on low‐power sensing applications. Measurements using a prototype device have been used to verify the authors simulations.